1987
DOI: 10.1121/1.394634
|View full text |Cite
|
Sign up to set email alerts
|

Difference limens for fundamental frequency contours in sentences

Abstract: Difference limens (DLs) for fundamental frequency (F0) of naturally spoken sentences were studied. The experiments can be classified into two major categories. In the first category the fundamental frequency of a portion of sentences of 2 to 3 s in duration was manipulated. The second set of experiments used very short sentences (‘‘The subject verb’’) in which the F0 of the entire sentence was manipulated. Across experiments, sentences of comparable length yielded similar DLs, except when the F0 was abruptly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…The imposition of sentence structure, with its linguistic content, added length, resynthesis uncertainty, and variety of possible contours and declinations, leads to much larger DLs than is found with short synthetic vowels. For vowels, the values are approximately 0.3 Hz (Flanagan & Saslow, 1958;Klatt, 1973) For phrases and sentences, however, at best, the DLs are in the range of 4-10 Hz (Harris & Umeda, 1987;Klatt, 1973;t'Hart, 1981). In addition, Rietveld and Gussenhoven (1985) found similar sensitivity to changes in prominence, approximately 1.5 ST. Interestingly, even the addition of a simple rising or falling contour on a vowel increases the DL to the 2-4 Hz range (Klatt, 1973), yet the shape of the contour (linear or parabolic) has minimal influence on perception (t 'Hart, 1991).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The imposition of sentence structure, with its linguistic content, added length, resynthesis uncertainty, and variety of possible contours and declinations, leads to much larger DLs than is found with short synthetic vowels. For vowels, the values are approximately 0.3 Hz (Flanagan & Saslow, 1958;Klatt, 1973) For phrases and sentences, however, at best, the DLs are in the range of 4-10 Hz (Harris & Umeda, 1987;Klatt, 1973;t'Hart, 1981). In addition, Rietveld and Gussenhoven (1985) found similar sensitivity to changes in prominence, approximately 1.5 ST. Interestingly, even the addition of a simple rising or falling contour on a vowel increases the DL to the 2-4 Hz range (Klatt, 1973), yet the shape of the contour (linear or parabolic) has minimal influence on perception (t 'Hart, 1991).…”
Section: Discussionmentioning
confidence: 94%
“…The DL for pitch in speech has been studied with a variety of stimuli, ranging from short vowel segments (Flanagan & Saslow, 1958;Klatt, 1973) to numbers, parts of sentences, and whole sentences (Harris & Umeda, 1987;Klatt, 1973;t'Hart, 1981). The imposition of sentence structure, with its linguistic content, added length, resynthesis uncertainty, and variety of possible contours and declinations, leads to much larger DLs than is found with short synthetic vowels.…”
Section: Discussionmentioning
confidence: 99%
“…Happy productions had higher pitch means ( happy , 416.74 Hz; sad , 255.72 Hz; paired t(23) = 57.74), larger standard deviations of pitch samples ( happy , 129.60 Hz; sad , 51.78 Hz; paired t(23) = 80.59), higher pitch maxima ( happy , 745.61 Hz; sad , 386.86 Hz; paired t(23) = 57.22), higher pitch minima ( happy , 210.80 Hz; sad , 163.33 Hz; paired t(23) = 7.06), greater intensities ( happy , 72.72 dB; sad , 71.26 dB; paired t(23) = 5.34), and greater durations ( happy , 3.30 seconds; sad , 3.24 seconds; paired t(23) = 3.08, all p < .01, all tests 2-tailed). Though all of these comparisons indicated statistically significant differences, it is unlikely that participants detected the between-condition differences in intensity and duration, because while these differences were consistent enough to be statistically significant, they were very small (e.g., in terms of JNDs, the mean pitch differences were probably at least 5 to 10 times greater than the amplitude or duration differences; Harris & Umeda, 1987; Miller, 1947; Abel, 1972). For example, the ratio of (log) durations for happy vs. sad productions was 1.00 (see Appendix 2).…”
Section: Methodsmentioning
confidence: 92%
“…17.3], and languages usually require a larger difference than the JND to maintain a phonological contrast; a 20-to 30-Hz difference (2-3 semitones in a comfortable pitch range for males from 150 to 170 Hz, 2.1 st, or for females from 200 to 230 Hz, 2.4 st) is just marginally sufficient [Hart, 1981]. Furthermore, Harris and Umeda [1987] found that JNDs are much greater in natural sentences. This is so even though the pitch JND for pure tones is fairly small, about 3 Hz for frequencies below 500 Hz [Kollmeier et al, 2008], i.e.…”
Section: Introductionmentioning
confidence: 98%